Big red lollipop - Khan, Rukhsana, 1962-; Blackall, Sophie (New York, N.Y. : Viking, 2010)
Having to take her younger sister along the first time she is invited to a birthday party spoils Rubina's fun, and later when that sister is asked to a party and baby sister wants to come, Rubina must decide whether to help.
A Junior Library Guild selection
Ages 4 up.
Accelerated Reader/Renaissance Learning
Keywords: Sisters -- Juvenile fiction; Birthdays -- Juvenile fiction; Parties -- Juvenile fiction; Conduct of life -- Juvenile fiction; Arab Americans -- Juvenile fiction; Sisters -- Fiction; Birthdays -- Fiction; Parties -- Fiction; Conduct of life -- Fiction; Arab Americans -- Fiction